Development and Evaluation of Gastroretentive Floating Bilayer Tablets Containing Ivabradine hydrochloride and Trimetazidine dihydrochloride - Jadhav, Sagar S. (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Unlike conventional angina treatment medicines, newer antianginals such as Ivabradine hydrochloride and Trimetazidine dihydrochloride displayed therapeutic potential without negative effects. However, IBH and TMZ both have shorter half-life and require multiple dosing. Literature study revealed that bilayer tablet of combination is not available. Hence, the objective of present research was to formulate and evaluate bilayer floating gastroretentive tablets with IBH immediate and TMZ floating release layer. Materials and Methods: Simple direct compression method and floating technique was employed. IBH and TMZ layer developed separately. IBH layer prepared using Avicel-112, Klucel EXF ultra, and Vivasol/Crosscarmelose sodium while TMZ layer developed using Kollidon SR, Benecel K 200 M, and Sodium bicarbonate. Best trials combined for the preparation of bilayer tablet. Tablets evaluated for pre-compression and post-compression parameters, floating time, floating lag time (FLT), total floating time swelling index, and matrix integrity. Results: Melting point, differential scanning calorimetry, and ultraviolet absorbance confirmed the identity and purity of drug. Fourier transform infrared spectrum of active pharmaceutical ingredient and drug mixture with excipients demonstrated the compatibility. IR layer trial I-4 showed passable flow with 3 s of disintegration time in distilled water and 100% drug release within 5 min. Floating layer trial T-8 showed fair flow characteristic, 15 s FLT, >24 h of total floating time and controlled the drug release more than 12 h without burst effect. Discussion: Preformulation study result revealed that the both the drug are pure form and compatible. For immediate release layer, Vivasol (Crosscarmelose) showed best disintegration and combination HPMC K200 M and Kollidon SR polymer with sodium carbonate provided controlled release with low FLT and high total floating time. Conclusion: Based on research findings, it can be concluded that bilayer gastroretentive tablets successfully formulated with IBH as IR layer and TMZ as floating layer. Combination of polymer needed for drug release control with tablet floatability. Hydrophilic polymer Benecel K200 M forms matrix channel which entrap sodium bicarbonate bubbles and tablet become buyant while Kollidon SR and stearic acid contributes in retardation of drug release.